Spectrometer for detailed study of radon and thoron system decay products - Frolov, O.S.; Sadovnichy, A.A.; Pavlenko, Yu.N.; Shevchenko, V.A.; Zaytsevsky, I.L.; Podviyaniuk, R.B.; Pavlenko, I.O. (Вопросы атомной науки и техники, 2004)
The results of development of an aspiration type spectrometer for investigation of daughter products of radon and thoron are presented. Main parameters of the device: active detector area of 32 cm2, air pumping through the filter up to 100 liters/min, energy resolution of the detection unit of 50…70 keV. Measurements are made both during the pumping and after the pumping. Accumulation, processing, representation and storage of data are made using a personal computer incorporated into the device. Setup and control of the device are made on the computer keyboard. The results of measurements of spectra of the radon and thoron system, including dependencies of α-activity of various radio-nuclides are shown. With this device it’s also possible to measure electron energy loss spectra.